Bayesian approach to AUC-guided vancomycin monitoring in Intensive Care Unit and Poison Control Department - Do , Tran Khanh Vy; Vo , Nguyen My Ngan; Nguyen , Nhu Minh; Le , Phuc Quynh Nhu; Le , Ba Hai; Vo , Thi Ha (Tạp chí Y Dược Huế, 2026)
Objectives: To compare AUC24 values between three vancomycin AUC estimation methods, including Bayesian two-concentration, Bayesian one-concentration, and first-order equations. Materials and methods: A cross-sectional, retrospective study of 67 medical records of adult patients who received vancomycin therapy drug monitoring based on AUC at the Intensive Care Unit - Poison Control Department, Nguyen Tri Phuong Hospital, from July 2023 to April 2024. Results: There was high agreement between Bayesian two-concentration and one-concentration methods (r = 0.974, clinical agreement 91%), and Bayesian twoconcentration method and first-order equations (r = 0.968, clinical agreement 83.6%) with a variability of 95% LOA -150.5 to 98.9 (MD = -25.8 mg.h/L) and 95% LOA -99.3 to 175.8 (MD = 38.3 mg.h/L), respectively. The Bayesian one-concentration and first-order equations had lower agreement than the other comparisons (r = 0.927, clinical agreement 80.6%), showing significant variability with 95% LOA -144.4 to 272.5 (MD = 64 mg.h/L). Conclusion: The Bayesian two-concentration and one-concentration methods demonstrated the highest agreement. The methods which had significant differences need to be considered for their interchangeability in clinical practice.